The Markets for Economic Governance in Social Market Economy Policy - Piotr WALĄG (Communications of International Proceedings, 2020)
This article presents the principles of interventionism in the light of the deliberations and actions of the Ordo Liberal economists - In Eucken. and L. Erhard - constructivist economic order. The consequences and coherence of the principles of economic order shaping economic policy are contrasted with the mistakes resulting from the discretionary practice of economic policy, within the framework of manifestations of state interventionism in the economy. In the conditions of globalisation in liberalising markets, the interpenetration of economic and political models (Anglo-American capitalism, the European model of the social market economy, Asian capitalism) is inevitable, in which the most important process is to direct economic interaction towards optimising economic and social utility. The organically shaped economic "order" (the rules of the market game) in liberalism differs significantly from the constructivist concept of conducting policy of shaping economic order in ordo liberalism.  The creation of a legal basis, rules of deception for free, equal and responsible individuals was supposed to be a tool for reversing the process of self-destruction of liberalism, to which the effects of boundless freedom in the operation of individuals were to lead (freedom in an extremely liberal view is a threat to itself). The construction of a competitive economic order developed as the foundations of ordo liberalism is perceived by the author of this article as the creation of rules / principles necessary to achieve the pro-effective and free market system goal. Particular emphasis within the framework of interventionism is placed not on the policy interfering directly in economic processes, but on the policy setting the rules / conditions of market play.  This article states that: economic transformation, seen in the light of the need for a faster pace of change, cannot be dissociated from the strong influence of the state in shaping economic order, and is therefore doomed to constructivism, and interventionism as the most effective but highly imperfect approach possible.
Keywords: Social Market Economy; Ordo Liberalism; Economic Governance; Systemic Transformation; Organic Constructivist Processes; Interventionism